Penilaian Rekomendasi Teknis Sebagai Pengendali Tata Guna Lahan di Kecamatan Magetan - Buanawan, Fendy Tri; Yuliastuti, Nany (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Magetan Subdistrict increased intensity of the development potential violations in construction. To prevent violations of applicable land use regulations to obtain Building Permit called Technical Recommendations which contains provisions - such provisions, Provisions Building, Line Worth. Objective studies examined the function, role and position of Technical Recommendation. The method used is descriptive analysis includes analysis of violations Technical Recommendation, analytical understanding of the citizens of the spatial and Technical Recommendations, performance analysis Technical Recommendation, the analysis of the potential of the region, the analysis of the effectiveness of the Technical Recommendation as controlling land use, while also using correlation analysis to determine relationship factors - factors influence the change of land use with the Product Moment correlation Analysis (Pearson). Results of the study is that the performance factor Technical Recommendation strong influence on land use changes in the district Magetan with a coefficient of 0.000 and a correlation coefficient Significance 0652. To factor people's understanding of spatial and technical recommendations have a very low correlation to changes in land use that with a correlation coefficient of each - each of 0138 and 0220. Violations are violations Line Border Fences and buildings, so that the Technical Recommendation is still not able to function as a controlling land use. Recommendations is necessary to improve the provisions of Technical Recommendation, more intensive socialization, supervision and control of the building in violation, as well as implementing enhanced performance.